2022
DOI: 10.3389/frsen.2022.861337
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential of Mobile Laser Scanning to Quantify Forest Structural Complexity

Abstract: Today, creating or maintaining forest structural complexity is a management paradigm in many countries due to the positive relationships between structural complexity and several forest functions and services. In this study, we tested whether the box-dimension (Db), a holistic and objective measure to describe the structural complexity of trees or forests, can be used to quantify the structural complexity of 14 European beech (Fagus sylvatica L.) dominated forest plots by means of mobile laser scanning (MLS). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…This is for several reasons: We used 35 scans during both campaigns, distributed in a similar pattern, and both scanners have a similar range (79 m for the Imager, 70 m for the Faro Focus M70). As shown by Neudam et al (2022), repeated laser scanning measurements that are based on similar scan designs result in comparable measures of structural complexity (boxdimension) if the resolution is not too fine. Here, we used a lower cutoff of 10 cm for the calculation of the box-dimension, thereby minimizing its dependency on the scanner's resolution (10,000 points per 360 • for the Z+F Imager in winter 2013, 10,240 points per 360 • for the Faro in winter 2021).…”
Section: Structural Development Of the Plot And The Individual Treesmentioning
confidence: 99%
“…This is for several reasons: We used 35 scans during both campaigns, distributed in a similar pattern, and both scanners have a similar range (79 m for the Imager, 70 m for the Faro Focus M70). As shown by Neudam et al (2022), repeated laser scanning measurements that are based on similar scan designs result in comparable measures of structural complexity (boxdimension) if the resolution is not too fine. Here, we used a lower cutoff of 10 cm for the calculation of the box-dimension, thereby minimizing its dependency on the scanner's resolution (10,000 points per 360 • for the Z+F Imager in winter 2013, 10,240 points per 360 • for the Faro in winter 2021).…”
Section: Structural Development Of the Plot And The Individual Treesmentioning
confidence: 99%
“…It is also conceivable that environmental influences such as slight leaf shaking, which cannot be avoided, even when there is no wind, could additionally amplify the noise. Neudam et al [20] and Guzmán et al [58] also concluded that leaf-bearing trees produce more scattered point clouds than leafless trees. At the stand level, occlusion is particularly evident in the canopy layer of beech trees (Figure 5).…”
Section: Seasonal Comparisonmentioning
confidence: 99%
“…Additionally, difficulties arise in obtaining detailed tree structures due to canopy occlusion [19]. Mobile laser scanners, on the other hand, are well suited for scanning forest stands and individual trees with a high level of detail, e.g., [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Box-dimension parameter ( Db ) is an integrative measure of tree architecture firstly suggested by Mandelbrot (Mandelbrot 1982). Considering the TLS technology potential for a 3D detailed analysis, Db was recently re-introduced by some authors (Seidel et al 2019; Heidenreich and Seidel 2022; Neudam, Annighöfer, and Seidel 2022). Db is a measure sensitive to both outer shape and internal structure of a tree.…”
Section: Package Overviewmentioning
confidence: 99%